The little Italian hotel - Patrick, Phaedra (Park Row, 2023)
Ginny Splinter, acclaimed radio host and advice expert, prides herself on knowing what's best for others. So she's sure her husband, Adrian, will love the special trip to Italy she's planned for their twenty-fifth wedding anniversary. But when Ginny presents the gift to Adrian, he surprises her with his own very different plan--a divorce. Beside herself with heartache, Ginny impulsively invites four heartbroken listeners to join her in Italy instead while live on air. From hiking the hills of Bologna to riding a gondola in Venice to sharing stories around the dining table of the little Italian hotel, Ginny and her newfound company embark on a vacation of fun, hope and self-discovery.